Mind-Reading Computers: towards a new horizon in Medical Science - Mitra, Soumi; Nath, Asoke (International Journal of Computer Sciences and Engineering, 2019)
Mind reading is the ability to infer other people’s mental state and use that to make sense of and predict their behaviour and intensions. Though it seems impossible to read someone’s mind, the modern neuroscience is able to do just that with the help of Mind Reading Computers. Over the years, many Brain Machine Interface (BMI) tools have been invented and they have been put to use in different areas of research, but the most effective and useful applications of mind reading computers probably have been in the field of medical science. Starting from mind controlled robotic arms for disabled persons to today’s ‘Neuralink’ which is expected to treat serious brain diseases, scientists have always been up to create better replacement for the current, conventional way of treatment in neurology with the help of mind reading computers. In the present paper the author discusses about how mind reading computers are being used in development of human health and wellness and also about the future scopes of the on-going researches in this field. The author has also tried to find out the risks related to BMI devices.